MODERN METHODS OF DIAGNOSIS AND TREATMENT OF CHRONIC ENDOMETRITIS, IN PREPARING PATIENTS FOR ASSISTED REPRODUCTIVE TREATMENT TECHNOLOGIES (LITERATURE REVIEW) - Chalova Leila,; Lokshin Vyacheslav,; Orazov Mekan,; Kim Tatyana,; Kinzhibayev Arman,; Rybina Anastassiya, (Academic Journal of Physical and Chemical Sciences, 2020)
Since the chronic endometritis often leads to impaired reproductive function causing infertility, failed IVF attempts, miscarriage, and complicated pregnancy and childbirth, it has become not only medically relevant but also socially significant. For successful embryo implantation, the thickness of the endometrium should be at least 7 cm. Even though there is always a chance for embryo implantation, despite the endometrial hypoplasia, the attachment may be fragile, and such pregnancy may cease its development further on. Recently, in connection with an increase in the rate of developing allergic reactions, dysbacteriosis, and the emergence of drug-resistant strains of microorganisms, a search for new treatment methods to avoid these complications has begun. One of such methods in treating chronic endometritis, satisfying several requirements (efficiency, comfort, accessibility, safety), is the ultrasonic cavitation of the uterine cavity.